Mortality Risk and Its Effect on Shortfall and Risk Management in Life Insurance - Gatzert, Nadine; Wesker, Hannah (Journal of Risk and Insurance, 2014)
Mortality risk is a key risk factor for life insurance companies and can have a crucial impact on its risk situation. In general, mortality risk can be divided into different subcategories, among them unsystematic risk, adverse selection, and systematic risk. In addition, basis risk may arise in case of hedging, for example, longevity risk. The aim of this article is to holistically analyze the impact of these different types of mortality risk on the risk situation and the risk management of a life insurer. Toward this end, we extend previous models of adverse selection, empirically calibrate mortality rates, and study the interaction among the mortality risk components in the case of an insurer holding a portfolio of annuities and term life insurance contracts. For risk management, we examine natural hedging and mortality contingent bonds. Our results show that particularly adverse selection and basis risk can have crucial impact not only on the effectiveness of mortality contingent bonds, but also on the insurer's risk level, especially when a portfolio consists of several types of products.
WiSo-Import:2015-03-26:3333
Keywords: Shortfall and Risk Management; mortality risk; Life insurance